The Enhancing Capsicum annuum L. Disease Resistance with Carrier and BSF Larval Gut Microbes - Nururrahmani, Azmah; Sanjaya, Yayan; Hernawati (Universitas Atma Jaya Yogyakarta, 2025)
Red chili (Capsicum annuum L.) is one of the essential vegetable commodities in Indonesia. Nevertheless, the production of red chili is affected by disease due to fungal infection. Previous research showed that the consortial formulation of bacterial and Trichoderma without a carrier from Black Soldier Fly (Hermetia illucens) larva gut enhanced the disease resistance of red chili. Regardless, the research has not overcome several diseases caused by fungal infection. This study aims to analyze the effect of adding kaolin, talc, and zeolite as carriers with bacterial and Trichoderma consortia from BSF larval gut on the disease resistance of red chili caused by fungal infection. This experimental study was carried out in a randomized block design. The treatments were consortial of bacterial and Trichoderma + carrier kaolin (BTrK), talc (BTrT), zeolite (BTrZ), positive control of consortial without a carrier (K+(1)), positive control of inorganic treatment (K+(2)), and negative control of plants without treatment (K(-)). The results were analyzed by calculating disease incidence (DI) and severity intensity (SI) scores to determine disease resistance. New findings prove that BTrK enhanced resistance to fungal infection, namely cercospora leaf spot, leaf rust, and powdery mildew. BTrT formulation enhanced resistance to symptom severity. The study concluded that carrier formulation enhanced the resistance of red chili.